2014
DOI: 10.1103/physrevstab.17.040702
|View full text |Cite
|
Sign up to set email alerts
|

Optical beam transport to a remote location for low jitter pump-probe experiments with a free electron laser

Abstract: In this paper we propose a scheme that allows a strong reduction of the timing jitter between the pulses of a free electron laser (FEL) and external laser pulses delivered simultaneously at the FEL experimental stations for pump-probe-type experiments. The technique, applicable to all seeding-based FEL schemes, relies on the free-space optical transport of a portion of the seed laser pulse from its optical table to the experimental stations. The results presented here demonstrate that a carefully designed lase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
38
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(38 citation statements)
references
References 21 publications
0
38
0
Order By: Relevance
“…It is demonstrated that at FEL experimental stations, the timing jitter generated due to a free space propagation of ~100 m and due to folding mirrors can be controlled with 5 fs accuracy via currently available technology3435.…”
Section: Resultsmentioning
confidence: 99%
“…It is demonstrated that at FEL experimental stations, the timing jitter generated due to a free space propagation of ~100 m and due to folding mirrors can be controlled with 5 fs accuracy via currently available technology3435.…”
Section: Resultsmentioning
confidence: 99%
“…Two bendable mirrors in Kirkpatrick-Baez configuration focused the x rays into a sub-100 µm spot. The same optical laser beam (λ = 780 nm) that seeds the FEL was used for pumping the sample, ensuring an extremely low jitter (<10 fs) between the pump and the probe [26,27]. The optical pump and the FEL probe beams were kept almost collinear (<2 • apart), introducing a negligible temporal spread over the measured area.…”
Section: Methodsmentioning
confidence: 99%
“…Optical transport of ultrashort pulses generated by optical laser from its optical table to the experimental stations, which are~100 m away, requires ultra-high vacuum transport system. S. Schulz et al [44] and P. Cinquegrana et al [45] have demonstrated that a carefully designed laser beam transport, including a free space propagation of 150 m and a number of beam folding mirrors allows one to keep the timing fluctuations to less than 4 femtoseconds RMS.…”
Section: Terawatt-attosecond Soft X-ray Pulse Generation Tables and Smentioning
confidence: 99%